Improving the Temperature Sensitivity of Bitumen for Emergency Pavement Repair - Al Hawesah, Hayder; Sadique , Monower; Harris, Clare; Al Nageim , Hassan; Stopp , Karl; Pearl, Harry; Shubbar, Ali (Periodica Polytechnica Civil Engineering, 2021)
The quality of asphalt pavement maintenance depends on several important factors, including the selection of patching materials and choice of repair technique. Conventional hot mix plants operate to support large paving projects, and economy favors high-volume output. When repairs and maintenance are needed it can be challenging to maintain small quantities of hot bituminous mixtures at a sufficient temperature, especially in the case of winter maintenance and consequently the repair materials cannot be compacted to the desired level in some occasions. The temperature sensitivity plays a significant factor to understand the asphalt pavement failures and indicates how quickly asphalt properties change over time in terms of indices such as penetration index. Therefore, this research aims to develop a polymer-modified binder with reduced temperature sensitivity, and it can be used for hand-laid application in small quantities for emergency winter repair and maintenance. The results showed that the highest penetration index has been achieved by modifying bitumen with 20% rubber and 2% wax, which is reduced the temperature sensitivity by 168%. Additionally, the Fourier Transform Infrared Spectroscopy (FTIR) test and X-Ray Diffraction (XRD) test were conducted to monitor the changes in the chemical composition and identify crystalline phases of polymer modified binder from the aspect of functional groups. It is indicated that the bitumen, rubber, and wax react chemically to build 3D networks that have an interlaced form in the bitumen matrix resulting in reduced temperature sensitivity of the polymer modified binder.